Consumers' adoption of wearable technologies: literature review, synthesis, and future research agenda. (2017) - Kalantari, Mahdokht
Wearables devices have emerged as rapidly developing technologies that have the potential to change people's lifestyles and improve their wellbeing, decisions, and behaviours as well as enhance core business processes. However, the adoption of these devices has been relatively slow when compared to mainstream technologies such as smartphones. Hence, manufacturers and designers show a growing interest to understand the influential factors in adopting these technologies. This will help them improve the features and desirability of these devices in order to wow the consumers and win them over. Researchers in various disciplines have studied consumers' adoption of wearable technologies, such as smart glasses and smartwatches using different theories and methodologies. The goal of this paper is to review and synthesise the literature of consumers' adoption of wearable technologies, review the applied technology diffusion and adoption theories, identify the influential factors in the adoption decision, and suggest directions for future research.